Heartbeat perception and panic disorder: possible explanations for discrepant findings. - Ehlers, A; Breuer, P; Dohn, D; Fiegenbaum, W (1995)
Results on cardiac awareness in panic disorder are inconsistent. The present study attempted to clarify whether differences in instructions or the inclusion of patients taking antidepressant medication could account for these inconsistencies. 112 patients with panic disorder with agoraphobia were compared to 40 normal controls on the heartbeat perception task developed by Schandry (1981) [Schandry, R., Psychophysiology, 18, 483-488] using a standard instruction ("count all heartbeats you feel in your body") and a strict instruction ("count only those heartbeats about which you are sure"). Superior heartbeat perception for patients was only found with the standard instruction. Similarly, only with the standard instruction, patients taking medication affecting the cardiovascular system performed worse than patients without medication, as expected based on the relationship between stroke volume and heartbeat perception. The pattern of group differences indicates that agoraphobic patients have a better feeling for how fast their heart is beating than controls although these differences may be due to a tendency to interpret weak sensations as heartbeats. Furthermore, we tested in a subgroup of 40 patients whether cardiac awareness changes with exposure treatment. No changes in heartbeat perception were observed.